Facile synthesis of urchin-like LaWO4Cl assemblies and their near-infrared photothermal conversion. Issue 30 (18th July 2019) - Sun, Lin; Shi, Yang; Tang, Mingcong; Wang, Dong; Tian, Yaping; Li, Jing
Abstract : The hierarchical urchin-like LaWO4 Cl assemblies promote the photothermal conversion performance due to the localized surface plasmon resonance. Abstract : The construction of the hierarchical nanostructures of inorganic materials with high stability has attracted great attention for photothermal therapy. In this paper, we presented the preparation of urchin-like LaWO4 Cl nanostructures assembled with nanoribbons via a facile solvothermal reaction. X-ray diffraction (XRD) analysis confirmed the formation of good crystalline urchin-like LaWO4 Cl assemblies. Energy dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS) revealed the element composition of the prepared urchin-like nanostructures. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the urchin-like LaWO4 Cl assemblies were composed of single crystalline nanoribbons with diameters less than 10 nm. When excited with an 808 nm near-infrared (NIR) laser at the power density of 1.91 W cm −2 for 5 min, the temperature quickly increased to 52 °C. The in vitro cytotoxicity of urchin-like LaWO4 Cl was tested with human cervical cancer cells (HeLa), revealing excellent biocompatibility. More importantly, the photothermal treatment with urchin-like LaWO4 Cl displayed great therapeutic efficacy in vitro . Thus, urchin-like LaWO4 Cl would be a new promising NIR light-driven photothermal agent, which can also pave a new way for the material design of PTT agents.